Desenvolvimento de curativos para cicatrização de feridas por segunda intenção baseados em biomateriais capazes de promoverem resposta celular controlada via estímulo externo - Carlos Ignacio (2009)
The high incidence of wound healing by second intention and the high costs associated with their treatment are changing the idea that healing dressing is just for wound protection but to accelerate cell proliferation and to provide good conditions for the skin recuperation. In this work, a new curative was develop that would be able, in the appropriate and programmed moment, to be removed from the new tissue through an external stimulus that would favor cellular detachment without extensive damages. We used for such, polymers based in poly (N-isopropylacrylamide} (P-N-IPAAm), that is sensitive to external stimulus. This polymer has a phase transition that turns it hydrophilic when it is used in temperatures below 32C and hydrophobic fortemperatures above 32C. The main hypothesis of this work involved the use of the behavior of this polymer in contact with the cells that participate in the wound healing process. While hydrophobic, the polymer can favor protein adhesion, however, when turned hydrophilic (below the transition temperature), it can lead to cellular detachment, the so called on-off mechanism. We prepared a wound dressing with two layers, beingthe first composed by a polyurethane film (PU) with 50m of thickness, whose function was the protection of the wound and the second composed by a micro layer of grafts of P-N-IPAAm, whose function is to provide good conditions for cellular activity and the mechanism on-off. Thermoplastic PU films were manufactured by lamination processand the P-N-IPAAm were grafted onto previously created reactive groups on the surface of the PU film. Two types of treatments were used to activate the surface: corona effect and the ultraviolet radiation. The treatment by ultraviolet radiation was shown to be easier to use and more efficient. The grafting process of P-N-IPAAm molecules was accomplished by radical polymerization in solution using ceric ammonium nitrate as the initiator. Layers ranging from 3 to 8 m of thickness of grafts were obtained. The transition LCST of P-N-IPAAm grafted to the PU was detected around 32C. This transition was monitored by checking the cloudy point of the film and by measuring thecontact angle as a function of the temperature. The mechanism on-off in vitro was studied by measuring the adsorption of albumin in temperatures above and below the LCST transition of P-N-IPAAm. Results showed that the grafted layer is able to display the on-off mechanism to allow the control of the process of albumin adsorption/desorption. They also took place tests of mechanism on-off in vivo through covering of lesion excisional done in mice type Swiss, being put the material in direct contact with the wound for three days and it was verified that the tissue was not adhered to the curative in the moment of the retreat of the curative. It was not possible to verify and to register the mechanism on-off of the curative, due to the fast decrease oftemperature of the skin mice after the anesthesia, there was fall temperature of the skin, registered in 28C that it is below LCST (32C), at this stage no adherence between the tissues and the curative could be noticed. Therefore to get more conclusive results it will be necessary to manipulate the LCST of the grafts for a temperature below 25C. However it was verified through histological analyses of cicatrization process, that wounds with curatives presented less intense inflammatory process and denser conjunctive tissue than the wounds without covering. The wounds with covered by PU with grafts showed signs of more intense re-epithelization and angiogenesis.